PENGARUH SOSIALISASI PERPAJAKAN DAN KINERJA ACCOUNT REPRESENTATIVE TERHADAP KEPATUHAN WAJIB PAJAK BADAN PADA KPP MADYA BANJARMASIN - Gustiana, Rara; Agustina, Ruslinda; Malinda, Ellsa Noor (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2023)
The aim of the research is to empirically prove the influence of tax socialization and account representative performance on corporate taxpayer compliance at the Banjarmasin Intermediate KPP. The method used in this research is a quantitative method by distributing questionnaires to 100 corporate taxpayers at the Banjarmasin Intermediate KPP who were used as respondents using the SPSS Version 26.00 test tool. Partial and simultaneous conclusions about tax socialization and account representative performance on corporate taxpayer compliance at KPP Madya Banjarmasin.